A study on effective adsorption of lead from an aqueous solution using Copper Oxide nanoparticles. Issue 1 (February 2021) - Zaidi, Rumman; Khan, Saif Ullah; Azam, Ameer; Farooqi, Izharul Haq
Abstract: In this work, the co-precipitation method was used to prepare copper oxide nanoparticles, which were found 21.6 nm in size, as calculated from the Debye-Scherrer equation. The prepared material was characterized using XRD and UV-Visible spectroscopy and further evaluated for its efficiency in adsorptive removal of Pb(II). To optimize the adsorption process was tried in the range: nanoparticle dosage (0.1-1 g/L), reaction time (0.5-2 hour), initial pH of the solution (2-6), and initial concentration of Lead (5-15 ppm). A linear fitting of equilibrium data to Langmuir and Freundlich isotherms was also explored and carried out. The results indicated that data obtained from the experiment fit better with the Freundlich isotherm model, attaining qmax for lead ions as 97 mg/g. Kinetic studies showed better fitting with a pseudo-second-order kinetic model signifying the mechanism of adsorption as chemisorption. The result advocate that synthesized adsorbent proved useful in adsorbing led from water.